Antioxidant and Antibacterial Activity of Plectaranthus amboinicus Leaf Extract - Islami, Deri; Teruna, Hilwan Yuda; Eryanti, Yum (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Plectranthus amboinicus (Lour.) is a perennial plant belonging to the family of Lamiaceae which have been widely used in traditional herbal medicine. In the present study, the extracts of the leaves of P. amboinicus that was extracted by different solvents were evaluated for their antioxidant and antibacterial properties. The fresh leaves of the plant were extracted using subsequent methanol, n-hexane and dichloromethane. The antioxidant activity was determined by DPPH free radical scavenging assay and the antimicrobial activity was tested against Escherichia coli and Staphylococcus aureus by agar well diffusion assay. The results of antioxidant activity test showed that dichloromethane extract of the leaves had the highest antioxidant activity among all with IC50 value of 50.2 μg/mL Methanol and n-hexane extracts were still active in DPPH with IC50 value of 71.3 μg/mL and 205.9 μg/mL, respectively. Furthermore, the dichloromethane and methanol ektracts have shown a promising antibacterial activity in E. coli. The findings indicated that dichloromethane and methanol extracts of the leaves of P. amboinicus were potential further study as herbal medicine as they showed high antioxidant and antibacterial activities.